2012
DOI: 10.4067/s0717-65382012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Population cytogenetics of the "Northern Mod 1" chromosomal race of Liolaemus monticola Müller & Helmich (Iguanidae) from Central Chile

Abstract: We report the "Northern 2n=38-40, modifi cation 1" race from three localities of the Liolaemus monticola complex in Chile that appears to be chromosomally and geographical intermediate between two previously described "Northern 2n=38-40" and "Multiple Fission, 2n=40-44 (MF)" races. This race retains the same "Northern" chromosomal features, but differs by being both polymorphic for an enlarged chromosome pair 6 and for a pericentric inversion in chromosome pair 7; these rearrangements are present in the "MF" r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
10
2
Order By: Relevance
“…A number of studies have been performed on chromosomes, coloration, diet, thermoregulation, and geometric morphometrics which have provided evidence for clinal variation of lizards in Chile (Lamborot 1991;Lamborot et al 2012;Vásquez et al 2007;Vidal et al 2007;Sepúlveda et al 2008;Fariña et al 2008;. In spite of these evidences, our results do not show clinal variation in head shape among the five studied localities of M. atacamensis.…”
Section: Discussioncontrasting
confidence: 56%
“…A number of studies have been performed on chromosomes, coloration, diet, thermoregulation, and geometric morphometrics which have provided evidence for clinal variation of lizards in Chile (Lamborot 1991;Lamborot et al 2012;Vásquez et al 2007;Vidal et al 2007;Sepúlveda et al 2008;Fariña et al 2008;. In spite of these evidences, our results do not show clinal variation in head shape among the five studied localities of M. atacamensis.…”
Section: Discussioncontrasting
confidence: 56%
“…Data on recombination patterns in reptiles remain scarce. Most studies used chiasma counts and distribution at diakinesis-metaphase I ( Cobror et al 1986 , Lamborot et al 2012 , Reed et al 1992 ). However, the resolution of chiasmata analysis is rather poor, because the chromosomes at metaphase I are condensed, making precise chiasmata localization along the chromosome difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported at least four major lineages allowing to infer strong phylogeographic structure within L. nigroviridis [27]; therefore, an increase taxon sampling seems recommendable to determine the position of the new proposed taxon (L. uniformis) related to its sister species (L. nigroviridis). The second model, L. monticola, is a saxicolous lizard species from the mediterranean Andes [32,33] and the Coast Range [34] in central Chile from between 600 m to 1900 m. This species displays an extensive variation and complexity in chromosome number in a latitudinal gradient [35,36], with riverine barriers playing a major role in the divergence of populations [37,38]. Phylogenetic inferences show that L. nitidus is sister to L. monticola [3,39].…”
Section: Introductionmentioning
confidence: 99%